Numerical Modeling of Radiographic Images as the Basis for Correctly Designing Digital Radiography Systems of Large-Sized Objects - Osipov S. P. Sergey Pavlovich; Chakhlov S. V. Sergey Vladimirovich; Kayralapov D. Daniyar; Sirotjyan E. V. Evgeniya Vladimirovna (2019, 2019)
Title screen